Using choice experiment for wastewater treatment and service valuation in Selangor, Malaysia - Munusami, Chandramalar; Zainudin, Norzalina; Govindan, Santhi; Md Yusop, Hamidah; Alwi, Shaliza (Sky Publishing Limited., 2023)
A functional and modern sewerage system is essential for ensuring that wastewater is appropriately treated before it is released into the drainage system or river. This research was done to assist related service providers and governmental organisations in identifying households' willingness to pay for enhanced wastewater treatment and services. Attributes such as (i) environmental improvement (sludge), (ii) additional monthly payment, (iii) distance of treatment plant (odour impact), (iv) standard time for repair (response time), and (v) river water quality (effluent) were selected based on Focus Group Discussions. Six hundred households in the Malaysian state of Selangor that had completed the Choice Experiment questionnaire. The quality of river water (effluent) is a vital attribute according to the implicit price of wastewater treatment service features based on Multinomial Logit regression. According to Compensating Surplus estimates, families are willing to spend a 54 premium over the market rate to acquire the additional services.